Perturbation walking effects on prefrontal cortical activation and walking performance in older women with and without osteoarthritis: a FNIRS study - Bishnoi, Alka; Hu, Yang; Hernandez, Manuel E. (Frontiers in Aging Neuroscience, 2024)
Perturbation walking (PW) has emerged as a promising intervention for improving gait, yet its impact on cortical control, especially in adults with osteoarthritis (OA), remains understudied. This study aimed to investigate the effect of PW on prefrontal cortical (PFC) activation in older women with and without OA. We hypothesized an increase in PFC activation during PW compared to comfortable walking (CW), with a higher increase in individuals without OA (HOA) relative to those with OA. Twenty community-dwelling older women (66.7 ± 5.41 years) participated in a perturbation walking task on an instrumented treadmill. Functional Near Infrared Spectroscopy measured PFC oxygenated hemoglobin (HbO2) and deoxyhemoglobin (Hb) levels at baseline and during tasks. Linear mixed effects models assessed cohort (HOA vs. OA), task (PW vs. CW), and their interaction on HbO2 and Hb levels. Significant differences in HbO2 and Hb levels were found between CW and PW tasks for both cohorts (P < .001) with a significant task by cohort interaction (P < .05). In addition, changes in walking performance were observed during and after PW, with increased stance time correlating with decreased PFC activation during PW. Results suggest increased PFC activation during PW and subsequent gait adaptation in both groups. However, higher activation in HOA during PW aligns with theories of mobility limitations affecting neural activation in older adults. Further exploration is needed to understand how pain, obesity, and mobility factors influence cortical control in older adults with and without OA.